Is obesity associated with poorer outcomes in patients undergoing minimally invasive mitral valve surgery?. (23rd September 2020) - Aljanadi, Firas; Toolan, Caroline; Theologou, Thomas; Shaw, Matthew; Palmer, Kenneth; Modi, Paul
Abstract: OBJECTIVES: High body mass index (BMI) makes minimally invasive mitral valve surgery (MIMVS) more challenging with some surgeons considering this a contraindication. We sought to determine whether this is because the outcomes are genuinely worse than those of non-obese patients. METHODS: This is a retrospective cohort study of all patients undergoing MIMVS ± concomitant procedures over an 8-year period. Patients were stratified into 2 groups: BMI ≥ 30 kg/m 2 and BMI ˂ 30 kg/m 2, as per World Health Organization definitions. Baseline characteristics, operative and postoperative outcomes and 5-year survival were compared. RESULTS: We identified 296 patients (BMI ≥30, n = 41, median 35.3, range 30–43.6; BMI <30, n = 255, median 26.2, range 17.6–29.9). The groups were well matched with regard to baseline characteristics. There was only 1 in-hospital mortality, and this was in the BMI < 30 group. There was no difference in repair rate for degenerative disease (100% vs 96.3%, P > 0.99 respectively) or operative durations [cross-clamp: 122 min interquartile range (IQR) 100–141) vs 125 min (IQR 105–146), P = 0.72, respectively]. There were only 6 conversions to sternotomy, all in non-obese patients. There was no significant difference in any other perioperative or post-operative outcomes. Using the Kaplan–Meier analysis, there was no significant difference in 5-year survival between the 2 groups (95.8% vs 95.5%, P = 0.83, respectively). CONCLUSIONS: In patients having MIMVS, there is insufficient evidence to suggest that obesity affects either short- or mid-term outcomes. Obesity should therefore not be considered as a contraindication to this technique for experienced teams.